2020
DOI: 10.18632/oncotarget.27434
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab is efficient and safe in patients with advanced cutaneous squamous cell carcinoma: a retrospective, multicentre study

Abstract: There is no standard of care for unresectable cutaneous squamous cell carcinoma (cSCC). Chemotherapy, alone or combined with radiotherapy, is commonly used mostly as palliative treatment; moreover, its poor safety profile limits its use most of the time, especially in elderly patients. Thus, alternative options are needed. Targeted molecular inhibitors, such as the epidermal growth factor receptor inhibitor cetuximab, seem promising, but data are limited. We retrospectively evaluated clinical outcomes of cetux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
(27 reference statements)
2
27
0
Order By: Relevance
“…Moreover, we showed that treatment with TA99 induced a greater DC infiltrate in B16 tumors. This finding is consistent with reports indicating that treatment with the anti-EGFR antibody cetuximab results in an increased NK cell mediated ADCC, which makes the tumor cells or their antigens more susceptible to phagocytosis by DC [ 16 , 17 ]. Further, it has been reported that resistance to immunotherapy may be due in part to defective recruitment of DC, downregulation of antigen processing and presentation, and thus reduced cross-priming [ 24 , 35 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, we showed that treatment with TA99 induced a greater DC infiltrate in B16 tumors. This finding is consistent with reports indicating that treatment with the anti-EGFR antibody cetuximab results in an increased NK cell mediated ADCC, which makes the tumor cells or their antigens more susceptible to phagocytosis by DC [ 16 , 17 ]. Further, it has been reported that resistance to immunotherapy may be due in part to defective recruitment of DC, downregulation of antigen processing and presentation, and thus reduced cross-priming [ 24 , 35 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Targeting tumor antigens with specific antibodies, such as anti-CD20 (rituximab), anti-HER2 (trastuzumab), anti-EGFR (cetuximab), is well-established and has been relatively successful in a number of cancers, via interference with cellular signaling, complement-mediated lysis, antibody-dependent cell-mediated cytotoxicity (ADCC), and/or antibody-dependent cell phagocytosis (ADDP) [ 12 14 , 16 , 17 ]. However, the use of these unmodified antibodies during the therapy of advanced solid tumors such as breast cancer, metastatic colorectal cancer and head and neck squamous cell carcinomas as monotherapy, result in a high proportion of tumors with primary and acquired resistance, and relatively low rates of lasting therapeutic responses [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some PI3K inhibitors produced little to no response against the cell lines, a likely result of isoform specificity that requires further investigation [ 33 ]. The anti-EGFR biologic Cetuximab is sometimes given to patients with advanced cSCC, achieving overall response rates approaching 50% [ 49 ]. However, there are multiple mechanisms by which downstream effectors of EGFR may become activated, including via PI3K [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The objective response rate (ORR) was 53% and 42%, respectively, at 6 and 12 weeks. The median progression-free survival (PFS) and overall survival were 9.7 months and 17.5 months, respectively [ 163 ].…”
Section: Treatment Of Csccmentioning
confidence: 99%